Health care utilization by veterans prescribed chronic opioids - Kay C; Wozniak E; Ching A; Bernstein J (Journal of Pain Research, 2018)
Cynthia Kay,1,2 Erica Wozniak,2 Alice Ching,1 Joanne Bernstein1 1Clement J Zablocki - Department of Medicine, 2Center for Patient Care and Outcomes Research, Medical College of Wisconsin, Milwaukee, WI, USA Purpose: Ambulatory resources such as telephone calls, secure messages, nurse visits, and telephone triage are vital to the management of patients on chronic opioid therapy (COT). They are also often overlooked as health care services and yet to be broadly studied. The aim of the present study was to describe the Veterans Affairs (VA) health care utilization by patients based on COT, type, and amount of opioids prescribed. Patients and methods: A retrospective chart review was done on 617 patients on COT at a VA primary care clinic. Instances of health care utilization (emergency department visits [EDVs], hospitalizations, clinic visits, telephone triage calls, telephone calls/secure messages/nurse visits) were obtained. Results: Patients were likely to have more telephone calls, secure messages, or nurse visits if they were prescribed a schedule II opioid or if they were on more than one opioid. Model-based results found that patients on COT were more likely to have EDVs, telephone triage calls, and clinic contact compared to patients who were not on chronic opioids. Conclusion: The results are despite having a Patient Aligned Care Team, which is the VA’s patient-centered medical home. This suggests that reducing health care utilization for patients on COT may not be possible with just a primary care involvement. Keywords: opioids, Veterans Affairs, primary care, chronic pain